Fedorova M. A. Elbel S., Hrnjak P. Performance optimization of two-stage compressor system using transcritical R744 / trans. from Engl. M. A. Fedorova - M. A. Fedorova (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The use of transcritical R744 systems has become increasingly popular in recent years in a variety of different applications. For applications that span a wide temperature range between the heat source and heat sink, the use of two-stage compressor results in numerous advantages in terms of efficiency and compressor discharge temperature. This paper presents experimental data for a transcritical R744 compressor system operating at high heat rejection temperatures. A comprehensive system model was developed and validated with the experimental results. Based on this, the simulation tool was used to further optimize the system design specifically to accommodate the two-stage compression process. The optimum heat transfer area distribution has been determined to simultaneously ensure efficient intercooling at intermediate pressure and gas cooling at the high-pressure level. Simultaneously, the system was also optimized with respect to optimal intermediate pressure and the results show that for this particular system, the optimum intercooler pressure deviated substantially from the standard design approach that uses the geometric mean between suction and discharge pressures